Rescission, cancellation and election - Masum, Ahmad; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan; Arowosaiye, Yusuf Ibrahim (CLJ Malaysia Sdn Bhd, 2024)
This chapter generally discusses some of the equitable remedies, i.e., rescission, cancellation and election, available under the Specific Relief Act 1950. Basically, rescission is a right of an aggrieved party to set aside a contract and place in a position like before entering into the contract. On the other hand, cancellation is sought to nullify a written document between the parties in order to make it inoperative and invalid. By election, an aggrieved party chooses between two inconsistent or alternative rights or claims. It refers to the choice of a contracting party to terminate or affirm, and subsequently, which remedy to pursue.